Report on some caridean shrimps (Crustacea: Decapoda) from Mayotte, southwest Indian Ocean - Li, Xinzheng; Cleva, Régis; Poupin, Joseph (Zootaxa, 2012)
The present paper reports on four families, 21 genera, 31 species of caridean shrimps, including Gnathophyllidae (1 genus,1 species), Hymenoceridae (1 genus, 1 species), Palaemonidae (17 genera, 28 species) and Thalassocarididae (1 genus, 1species). All the species with exception of Urocaridella antonbrunii are reported for the first time from Mayotte. The colouration of six species are provided for the first time.